2021
DOI: 10.21037/atm-20-7715
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in ocular demodicosis: Demodex profiles and clinical manifestations

Abstract: Background: Demodex infestation is highly age-dependent. Intriguingly, our previous studies that focused on children and young adult patients suggested that the clinical features of young patients were different from those studies enrolling mainly elderly patients. Whether age plays a role between young and elderly patients with ocular demodicosis remains unclear.Methods: This prospective comparative study included 91 patients younger than 35 years and 92 older than 45 years with ocular demodicosis. Demodex mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 34 publications
0
13
2
Order By: Relevance
“…Previous studies reported that D. brevis was often found in young patients and significantly correlated with corneal involvement [ 28 , 34 ]; however, this was not consistent with our results. This may be because D. folliculorum and D. brevis were not distinguished from each other, and patients with keratitis were excluded from our research.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Previous studies reported that D. brevis was often found in young patients and significantly correlated with corneal involvement [ 28 , 34 ]; however, this was not consistent with our results. This may be because D. folliculorum and D. brevis were not distinguished from each other, and patients with keratitis were excluded from our research.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be because the young patients were in the early stages of Demodex infestation, with it lasting only a short duration, and the number of mites was small. Previous studies reported that D. brevis was often found in young patients and significantly correlated with corneal involvement [28,34]; however, this was not consistent with our results. This may be because D. folliculorum and D. brevis were not distinguished from each other, and patients with keratitis were excluded from our research.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations